A novel approach for detecting viable and tissue‐specific circulating tumor cells through an adenovirus‐based reporter vector. Issue 13 (25th July 2014) - Wu, Ping; Sokoll, Lori J.; Kudrolli, Tarana A.; Chowdhury, Wasim H.; Ma, Rong; Liu, Minzhi M.; Rodriguez, Ronald; Lupold, Shawn E.
<x xml:space="preserve">Abstract</x> BACKGROUND Circulating tumor cells (CTCs) hold great promise as biomarkers and are a direct source of tumor cells through a simple blood draw. However, CTCs are rare and their detection requires sensitive and specific methods to overcome the overwhelming hematocyte population. Therefore, CTC detection remains technically challenging. METHODS An assay was developed for detecting viable and tissue‐specific CTCs using a tropism‐enhanced and conditionally replicating reporter adenovirus (CTC‐RV). Adenoviral replication was made prostate‐specific by placing the E1A gene under the control of the probasin promoter and prostate‐specific antigen enhancer (PSE‐PBN). Viral tropism was expanded through capsid‐displayed integrin targeting peptides. A secreted reporter, humanized Metridia Luciferase (hMLuc), was engineered for expression during the major late phase of viral replication. The assay involves red blood cell lysis, cell collection, viral infection, and subsequent quantification of reporter activity from cellular media. Assay and reporter stability, cell specificity and sensitivity were evaluated in cell dilution models in human blood. RESULTS A conditionally replicating prostate‐selective adenovirus reporter and CTC assay system were generated. The secreted reporter, MLuc, was found to be stable for at least 3 days under assay conditions. CTC detection, modeled by cell dilution in blood, was selective for androgen receptor positive prostate cancer (PCa) cells. Serial dilution demonstrated assay linearity and sensitivity to as few as three cells. Prostate cancer cell viability declined after several hours in anticoagulated blood at ambient temperatures. CONCLUSIONS Conditionally replicative adenoviral vectors and secreted reporters offer a functional method to detect viable CTCs with cell specificity and high sensitivity. Prostate 74: 1286–1296, 2014. © 2014 Wiley Periodicals, Inc.